PEMANFAATAN TUTUP BOTOL MENJADI GANTUNGAN KUNCI MELALUI SOSIALISASI SAHABAT SAMPAH - Ikhyak Ulumudin; Novika Eila Ramadhani; Novita Ayuning Fitriani; Rohmiatul Aulia; Tri Melinda; M Wildan Falatehan Akbar; Nadia Fitrotul Aida; Muhammad Faiz; Nofi Silfiana; Nauval Mahendra Kusuma; Larasati Alifia N H (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2026)
Community Service (KKN) is one of the implementation of the Tri Dharma of Higher Education in the field of community service. This KKN activity was carried out in Klego Village, targeting students of SDN Klego 4. The problem found was the children's low awareness of and management of plastic waste, especially beverage bottle caps. Therefore, KKN students initiated a socialization activity for the Friends of Trash Socialization, followed by the use of bottle caps to make key chains as a medium for education and creativity for students. This activity aims to instill the use of plastic waste from an early age and increase students' awareness of the use of plastic waste. The methods used were socialization and direct practice. The results of the activity showed an increase in students' understanding of waste as well as increased creativity and concern for the environment. This activity is expected to become a means of continuous education for students of SDN Klego 4.